Operando X-ray absorption spectroscopic studies of the carbon dioxide reduction reaction in a modified flow cell. Issue 9 (2nd March 2022) - Hung, Sung-Fu; Wu, Feng-Yi; Lu, Yi-Hsuan; Lee, Tsung-Ju; Tsai, Hsin-Jung; Chen, Pei-Hsuan; Lin, Zih-Yi; Chen, Guan-Lin; Huang, Wen-Yang; Zeng, Wen-Jing
Abstract : Operando XAS reveals that the copper catalysts undergo a remarkable reduction to the metallic state during CO2 RR. Abstract : We have developed a flow cell for the operando X-ray absorption spectroscopy of CO2 RR, providing an identical catalytic environment as that of the electrochemical measurement. Two model catalysts, metallic copper and copper hydroxide, are investigated. These catalysts undergo a remarkable reduction to the metallic state in the flow cell during CO2 RR.